Meningkatkan Hasil Belajar Fiqih Siswa Madrasah melalui Penerapan Metode Pembelajaran Demonstrasi Materi Haji dan Umrah - Muhammad Barid; Pasmah Chandra (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: This study aimed to improve students’ learning engagement and outcomes by implementing the Demonstration Method in Fiqh instruction. Method: This study employed Classroom Action Research (CAR), consisting of two cycles: planning, action, observation, and reflection. The participants were eighth-grade students at MTTS Al Hasanah Bengkulu Tengah. Data were collected through classroom observations and learning achievement tests and analysed using descriptive quantitative methods. Results: The findings demonstrated a substantial improvement in both student engagement and learning outcomes. Learning mastery increased from 40.84% in the pre-cycle stage to 73.68% in Cycle I and 92.11% in Cycle II, exceeding the success criterion of 75%. Student engagement also improved from 50.00% in the pre-cycle stage to 76.92% in Cycle I and 90.38% in Cycle II, surpassing the established indicator of 70%. Conclusion: The Demonstration Method effectively enhanced student engagement and learning outcomes in Fiqh, particularly in the Hajj and Umrah unit. Contribution: This study provides empirical evidence supporting the use of demonstration-based learning as an effective instructional strategy for promoting active participation and improving learning achievement in Islamic education.